Analysis of Cobalt(II) and Nickel(II) in Water Medium using Voltammetry Techniques - Devi Aliefiyardi Aulia Widowati; Fanny Kurniawan; Shynta Ramadhan (Chemistry and Materials, 2023)
Currently, the electrochemical method as one of the fast, accurate, and reliable techniques for detecting heavy metals such as Co and Ni has been widely developed. Cyclic voltammetry methodology was successfully employed for determination of trace cobalt (Co) and nickel (Ni). Co and Ni levels are studied because they can cause water pollution and can be toxic, and non-biodegradable which influences the health of living things. To obtain results with high accuracy, this study tested several electrochemical parameters. Based on the results processed, the CoNi level in the solution can be measured well in the voltage range, scan rate, and pH of the solution, respectively, at -1.00 V to 0.75 V, 250 mV/s, and pH 3 (Ni) and pH 7 (Co). This work have been validated and showed good results with correlation coefficients of Co and Ni. The detection limit and quantity limit for Co and Ni were 510.2 ppm and 723.5 ppm, respectively, with 274.99 ppm and 916.66 ppm. Co and Ni metal RSDs also showed good values (<5%). In this study, Co and Ni levels in lab waste obtained by the cyclic voltammetry method were 510.2 ppm and 1666.47 ppm, and the results obtained from atomic absorption spectroscopy (AAS) measurements of 510.7 ppm and 1676 ppm. The developed electrochemical systems based are giving new inputs to the existing devices or leading to the development of novel heavy metal detection tools with interest for applications in fields such as environmental, safety, security controls or other industries.